Mortality due to bleeding, myocardial infarction and stroke in dialysis patients. (22nd August 2018) - Ocak, G.; Noordzij, M.; Rookmaaker, M. B.; Cases, A.; Couchoud, C.; Heaf, J. G.; Jarraya, F.; De Meester, J.; Groothoff, J. W.; Waldum‐Grevbo, B. E.; Palsson, R.; Resic, H.; et al.
Abstract : Essentials Mortality due to bleeding vs. arterial thrombosis in dialysis patients is unknown. We compared death causes of 201 918 dialysis patients with the general population. Dialysis was associated with increased mortality risks of bleeding and arterial thrombosis. Clinicians should be aware of the increased bleeding and thrombosis risks. Summary: Background: Dialysis has been associated with both bleeding and thrombotic events. However, there is limited information on bleeding as a cause of death versus arterial thrombosis as a cause of death. Objectives: To investigate the occurrence of bleeding, myocardial infarction and stroke as causes of death in the dialysis population as compared with the general population. Methods: We included 201 918 patients from 11 countries providing data to the ERA‐EDTA Registry who started dialysis treatment between 1994 and 2011, and followed them for 3 years. Age‐standardized and sex‐standardized mortality rate ratios for bleeding, myocardial infarction and stroke as causes of death were calculated in dialysis patients as compared with the European general population. Associations between potential risk factors and these causes of death in dialysis patients were investigated by calculating hazard ratios (HRs) with 95% confidence intervals (CIs) by the use of Cox proportional‐hazards regression. Results: As compared with the general population, the age‐standardized and sex‐standardized mortality rate ratios in dialysis patients were 12.8 (95% CI 11.9–13.7) for bleeding as a cause of death (6.2 per 1000 person‐years among dialysis patients versus 0.3 per 1000 person‐years in the general population), 13.4 (95% CI 13.0–13.9) for myocardial infarction (22.5 versus 0.9 per 1000 person‐years), and 12.4 (95% CI 11.9–12.9) for stroke (14.3 versus 0.7 per 1000 person‐years). Conclusion: Dialysis patients have highly increased risks of death caused by bleeding and arterial thrombosis as compared with the general population. Clinicians should be aware of the increased mortality risks caused by these conditions.